Kualitas Pelayanan Vaksinasi Covid – 19 Terhadap Kepuasan Masyarakat Umum di DKI Jakarta - Cindy Emileni M; Maulana Rifai; Dewi Noor Azijah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The implementation of the covid-19 vaccination is the right step taken by the government to break the ropes of the spread of the corona virus in Indonesia, especially in areas with high cases of COVID-19 spread, therefore a maximum quality of service is needed in accordance with the standards that have been set to obtain community satisfaction so that The dose of Covid-19 vaccination is increasing. This study uses a survey method with a quantitative approach. The research target is the general public in DKI Jakarta, with a sample of 100 people. The data analysis used is validity, reliability, classical assumption test and hypothesis testing. The results of this study have resulted in a significant influence between service quality and community satisfaction with results of 0.000 < 0.05, especially in the provision of covid-19 vaccination to the general public in DKI Jakarta. The correlation coefficient test is 0.757 strong and the determination test is 0.574 which shows the effect between variables is 57.4%. The influence of service quality on community satisfaction is positive or in the same direction so that the higher the quality of service, the higher the community satisfaction.